The impact of monetary policy in price and exchange rate stability in Suriname - Jahangir, Saira ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Deals with the central bank's contribution in achieving price and exchange rate stability in Suriname during the period 1991-1995.